2016
DOI: 10.1038/s41551-016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Solid stress and elastic energy as measures of tumour mechanopathology

Abstract: Solid stress and tissue stiffness affect tumour growth, invasion, metastasis and treatment. Unlike stiffness, which can be precisely mapped in tumours, the measurement of solid stresses is challenging. Here, we show that two-dimensional spatial mappings of solid stress and the resulting elastic energy in excised or in situ tumours with arbitrary shapes and wide size ranges can be obtained via three distinct and quantitative techniques that rely on the measurement of tissue displacement after disruption of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
354
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 334 publications
(378 citation statements)
references
References 46 publications
(54 reference statements)
24
354
0
Order By: Relevance
“…The resulting range of elastic moduli of 1.5 to 7.5 kPa (assuming E = 3xG’) from these studies is physiologically relevant, as it is similar to the range of stiffening previously reported in mouse models of pancreatic ductal adenocarcinoma [32]. Solid tumors also show an increase in elastic energy, independent of stiffness [33]. This mechanically-tunable aECM provides a facile approach for investigating the roles of both stiffness and viscoelasticity on cellular behavior.…”
Section: Discussionsupporting
confidence: 72%
“…The resulting range of elastic moduli of 1.5 to 7.5 kPa (assuming E = 3xG’) from these studies is physiologically relevant, as it is similar to the range of stiffening previously reported in mouse models of pancreatic ductal adenocarcinoma [32]. Solid tumors also show an increase in elastic energy, independent of stiffness [33]. This mechanically-tunable aECM provides a facile approach for investigating the roles of both stiffness and viscoelasticity on cellular behavior.…”
Section: Discussionsupporting
confidence: 72%
“…We subsequently showed that losartan and lisinopril, an angiotensin converting enzyme inhibitor (ACEi), decreased not only collagen but also hyaluronan, and enhanced the efficacy of low molecular weight chemotherapeutics in desmoplastic mice tumors(6). This benefit was in part due to the decompression of blood vessels resulting from decreased solid stress(7,8). The safety and low cost of ARBs and ACEis, together called angiotensin system inhibitors (ASIs), along with their potentiation of conventional chemotherapy make a strong case for repurposing ASI as adjuncts in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the ECM together with proliferating tumour and stromal cells leads to accumulation of independent of IFP, which compress vessels 29,40,41 . These forces have been quantified using mathematical modelling and 41,42 . Depletion of tumour cells, cancer-associated fibroblasts (CAFs), or ECM showed that all three components contribute to solid stress accumulation in tumours in mice 40,41 .…”
Section: Physical Microenvironment Of the Tumourmentioning
confidence: 99%